Perianal Paget's disease: case report and review of the literature. Issue 3 (3rd May 2016) - Bontinck, H.; Bontinck, J.; Rondou, T.; Pattyn, P.; Lockefeer, F.
Abstract: A peri-anal skin lesion, often eczema-like and with symptoms of pruritus, that does not resolve after classical local therapy should be biopsied. We present a case of peri-anal extramammary Paget's disease (EMDP) and associated anal adenocarcinoma. Reviewing the literature, more than 30% of patients with EMDP present a second primary tumour in their past, present or future history. In Europe, the risk of developing a new primary tumour in patients with this condition is increased compared with the standard population. In cases of peri-anal Paget's disease (PPD), specific histochemical markers allow us to differentiate between a primary and a secondary form, the secondary one is strongly associated with colorectal and anal tumours. We provide information about the most commonly suggested therapy for PPD with or without associated malignancy and about the recommended follow-up.